Kajian Pemilihan Koefisien Situs pada Perhitungan Spektra Percepatan Gerakan Tanah di Permukaan - Partono, Windu; Irsyam, Masyhur; Sengara, I Wayan; Asrurifak, Muhammad (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
SNI 1726:2012 states that surface spectral accelerations SMS (0.2 second) and SM1 (1 second) can be calculated by multiplying site factors Fa (0.2 second) and Fv (1 second) with spectral accelerations SS (0.2 second) dan S1 (1 second). All site factors used by SNI 1726:2012 are adopted from ASCE/SEI 7-10.  In 2013 Stewart and Seyhan proposed new and different site factors compared to ASCE/SEI 7-10. These site factors are then used for developing ASCE/SEI 7-16 with minor improvement for site class SE (soft soil). ASCE/SEI 7-16 states that the site factors for site class SE with SS greater than 1g or S1 greater than 0.2g, shall be calculated using Site Specific Analysis (SSA). The SSA method used for calculating site factor is difficult for ASCE/SEI 7-16 to be implemented in Indonesia. This paper describes the result of SMS and SM1 study at five cities (Jakarta, Bandung, Semarang, Yogyakarta and Surabaya) for site class SC, SD and SE using site factors proposed by Stewart and Seyhan and site factor SNI 1726:2012. The SMS and SM1 at five cities calculated using site factors proposed by Stewart and Seyhan are ±15% differences compared to SMS and SM1 calculated usingSNI 1726:2012 site factors.